The Education and Employment Effects of DACA, In-State Tuition and Financial Aid for Undocumented Immigrants - Lisa Dickson; T. H. Gindling; James Kitchin (Institute of Labor Economics (IZA), 2017)
Many undocumented immigrants come to the U.S. as children. Undocumented immigrant children have a legal right to attend free public primary and secondary schools. However, in most states undocumented immigrants are treated as out-of-state students in public colleges and universities, and are therefore required to pay substantially higher tuition than other state residents. Since 2001, 21 of 50 U.S. states have implemented policies that allow undocumented immigrants to qualify for in-state resident tuition (ISRT) at public colleges and universities. In 12 of these states undocumented immigrants are also eligible for financial aid. In this study we present strong evidence that both ISRT policies and access to financial aid significantly increase the college enrollment and graduation rates of undocumented immigrants but have no impact on the college enrollment or graduation rates of U.S.-born youth. Another important change in immigration policy that affects many undocumented immigrant children is the 2012 Deferred Action for Childhood Arrivals (DACA). DACA allows undocumented individuals who came to the U.S. as children to obtain legal employment. The potential of being able to work legally in the United States could represent a significant increase in earnings as well as a substantial increase in the perceived benefits of higher education. Our findings present evidence that DACA led to an increase in youth employment and a decrease in college enrollment rates. Further, we find no evidence that the introduction of DACA reduced or increased the positive impact of ISRT and financial aid policies.
Keywords: I23; J61; 330; higher education; undocumented immigrants; tuition policies at public universities